Community Empowerment in Tonjong Area Through Financial Application Training, “SIAPIK” - Puspitasari, Nindya Farah Dwi; Hendrian; Riyani, Etik Ipda; Idrus, Olivia (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
Badan Usaha Milik Desa (BUMDes) are one form of economic development in rural areas that the government is currently intensively undertaking. One of the rural areas that already has its own BUMDes in Bogor Regency is Tonjong Village. The purpose of this Community Service is to empower community in Tonjong Village in the field of financial reporting by utilizing the financial application, namely Sistem Informasi Aplikasi Akuntansi Pencatatan Informasi Keuangan (SIAPIK). The benefits obtained from the implementation of this community empowerment are encouraging the maximization of the business units of the Tonjong Village community, especially BUMDes Kurnia Abadi through good financial reporting so that their business can operate in accordance with BUMDes values, namely Tariffs (Transparency, Accountability, Responsibility, Independence, and Fairness). The method used to empower residents of Bogor Regency, especially those affected by the Covid-19 pandemic, is to prepare learning materials in the form of manual books and video tutorials on how to use the SIAPIK through simulation of company financial transactions that are similar like real conditions. Furthermore, in the learning process, several learning methods are used, including the distribution of manual books, demonstrations through video tutorials, and discussions via short messages.